2016
DOI: 10.1902/jop.2016.160226
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Dental Implant Placement in Atrophic Edentulous Mandibles: Vertical Bone Augmentation and Alternative Treatments. A Meta‐Analysis of Randomized Clinical Trials

Abstract: Short implants in the posterior area of the mandible seem to be preferable to vertical augmentation procedures, which present similar implant and prosthetic failure rates but greater morbidity. All the vertical augmentation technique comparisons showed similar intergroup results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 53 publications
0
30
2
1
Order By: Relevance
“…Multiple studies have reported that bone augmentation procedure for implants was not shown favorable outcomes due to the high rate of postoperative complications and risk factors . However, we found that bone augmentation procedure was more beneficial at the single missing tooth area in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Multiple studies have reported that bone augmentation procedure for implants was not shown favorable outcomes due to the high rate of postoperative complications and risk factors . However, we found that bone augmentation procedure was more beneficial at the single missing tooth area in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…The peculiarity of this study lies in the marked difference in the implant length between the test and control groups, namely a minimum of 4 mm. Preceding investigations comparing short implants to long implants, being either ≤8 mm versus >8 mm (Camps-Font et al, 2016;Lee et al, 2014) or ≤8 mm versus ≥9.3 mm (Tong et al, 2017), may not have been able to distinguish the variations or common treatment impacts across different studies. Additionally, the recent publication of several RCT's (Bechara et al, 2017;Bolle et al, 2018;Felice et al, 2018;Gastaldi et al, 2017Gastaldi et al, , 2018Naenni et al, 2018;Pohl et al, 2017;Rossi et al, 2015;Sahrmann et al, 2016) has allowed for a more efficient analysis of the scientific evidence in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews comparing short implants (≤8 mm) with long implants (>8 mm) placed after bone augmentation procedures found comparable survival rates, as well as less complications attributed to the short implants (Camps‐Font et al., ; Fan, Li, Deng, Wu & Zhang, ). However, this could be imputed to the small difference in implant length between the test and control groups.…”
Section: Introductionmentioning
confidence: 95%
“…It is generally claimed that short implants have been associated with lower survival rates than standard length implants [32,33]. However, more recent studies revealed no apparent difference in performances between short and long implants, and suggested that the use of short implants may be a viable and effective alternative treatment option [17,34]. These results seem to be due to the technical innovations in both the surface characteristics and geometry (macro-and micro-) design of the implant, which helped to compensate for the unfavorable crown-to-implant ratio and lower surface area available for bone to implant contact [35].…”
Section: Short Implants and Implant Stabilitymentioning
confidence: 99%